New approach for modelling size selectivity in shrimp trawl fisheries - Larsen, Roger B.; Herrmann, Bent; Sistiaga, Manu Berrondo; Brinkhof, Jesse; Tatone, Ivan; Langård, Lise (ICES Journal of Marine Science, 2017)
In the deep sea trawl fishery targeting shrimp (Pandalus borealis) and other cold-water shrimp species, fishers often use a Nordmöre sorting grid ahead of a small mesh codend to avoid bycatch. However, small fish can pass through the grid and are subsequently retained in the codend. This makes shrimp size selection complex and the size-dependent curve for both the shrimp and the bycatch species often exhibits a bell-shaped signature. In this study we developed a new model and method to estimate size selection in this fishery, conducted fishing trials in the Northeast Barents Sea, and applied the new method to quantify the individual and combined size selection of the Nordmöre grid and codend for deep water shrimp and two bycatch species. The size selectivity for both bycatch species showed the expected bell-shaped signature with low retention probability of very small and larger fish. The Nordmöre grid had high passage probability for all sizes, although it decreased slightly for the largest shrimps. The smallest shrimps were released by the codend.